Analisis Biaya pada Implementasi Resource Leveling Tenaga Kerja - Sholeha, Suviatus; Kamandang, Zetta Rasullia (Universitas Ibn Khaldun, 2024)
Construction projects are complex jobs within a certain period of time involving many resources such as materials, machines, methods, money, and manpower. Manpower is one of the resources with limited supply, high cost, and often causes problems due to fluctuations. Manpower needs to be analyzed for costs and distribution using the resource leveling method with the help of software in order to obtain the most efficient results. Manpower analysis was conducted under planning conditions, real implementation in the field, and after leveling. Labor allocation at planning (120 days) produced a graph with sharp fluctuations. There is a manpower allocation that exceeds the maximum capacity of daily manpower, making it inefficient. The highest manpower allocation was 167 workers/day, 9 masons/day, 43 carpenters/day, and 35 ironworkers/day at a total cost of Rp1,015,560,000. Meanwhile, the conditions in the field (120 days) equated to a daily manpower requirement of 55 workers/day, 4 masons/day, 16 carpenters/day, and 14 ironworkers/day at a total cost of Rp1,149,600,000. Meanwhile, the allocation of manpower must also take into account the type and volume of work to be completed. Furthermore, based on the results of the resource leveling study (144 days), a labor allocation with a low fluctuation graph was obtained. The allocation of labor is well distributed and no one exceeds the maximum capacity of daily manpower so that it is more efficient. It takes a total labor cost of Rp1,015,920,000. The comparative results of the three conditions have significant disparities. Labor after leveling results in the most efficient allocation. Meanwhile, labor before leveling results in the most efficient cost. Key words: Resource Allocation, Resource Leveling, Manpower Cost.